1995
DOI: 10.1006/inco.1995.1165
|View full text |Cite
|
Sign up to set email alerts
|

Connection Management Without Retaining Information

Abstract: Managing a connection between two hosts in a network is an important service to provide in order to make the network useful for many applications. The two main sub-problems are the management of serial incarnations of a connection and the transfer of messages within an incarnation. This paper investigates whether it is necessary for connection management protocols to retain state information across node crashes and between incarnations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Later, Fekete et al [1993] showed that no Data Link protocol could work correctly under these assumptions. Attiya et al [1995] proved a similar result regarding Transport protocols. In this paper, we investigate the power of crash failures for protocols other than Data Link and Transport protocols.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Later, Fekete et al [1993] showed that no Data Link protocol could work correctly under these assumptions. Attiya et al [1995] proved a similar result regarding Transport protocols. In this paper, we investigate the power of crash failures for protocols other than Data Link and Transport protocols.…”
Section: Introductionsupporting
confidence: 59%
“…For example, Attiya et al [1995] introduce a grace period between crashes. They also introduce a third way to change the assumptions by assuming that links have bounded capacity.…”
Section: Designing Correct Protocols That Are Resilient To Crashesmentioning
confidence: 99%
“…Self-stabilizing β-synchronizer We use a message passing version of the β-synchronizer that appears in [6]. The fact that we use the synchronizer in a message-passing system requires the use of a self-stabilizing end-to-end protocol (see e.g., [2,6,11]). …”
Section: Hypertree Global Maintenancementioning
confidence: 99%
“…Since R takes no steps in pump ; k and no packets are lost, S 1 ; : : : S k are in transit after pump ; k sender ; k. 5. Clearly none of the network assumptions satis ed by are violated; HA1 is satis ed because of the Dis events at the beginning of ; HA2 is vacuously true because the schedule is not fair packets are in transit.…”
Section: Pumpingmentioning
confidence: 99%
“…I.e., the network delivers in nitely many packets in each direction. 5 NA3. For every pre x of the schedule and X 2 f S; Rg:…”
Section: Na2mentioning
confidence: 99%